2016
DOI: 10.4238/gmr.15016933
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperbaric oxygen on the Nrf2 signaling pathway in secondary injury following traumatic brain injury

Abstract: ABSTRACT. We investigated the effects of hyperbaric oxygen treatment on the Nrf2 signaling pathway in secondary injury following traumatic brain injury, using a rat model. An improved Feeney freefall method was used to establish the rat traumatic brain injury model. Sixty rats were randomly divided into three groups: a sham surgery group, a traumatic brain injury group, and a group receiving hyperbaric oxygen treatment after traumatic brain injury. Neurological function scores were assessed at 12 and 24 h afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
(10 reference statements)
0
15
0
Order By: Relevance
“…When Nrf2 is up-regulated and translocated into the nucleus from the cytoplasm under stress conditions, the process is also essential for the activation of HO-1 expression (Kang et al, 2015). Growing evidence demonstrated that the Nrf2/HO-1 signaling pathway participated in the process of oxidative stress in several brain dysfunctional diseases (Meng et al, 2016; Bellaver et al, 2017; Zhao et al, 2018). Several antioxidant ingredients indicated that they protected cell damage by up-regulating Nrf2 and HO-1 expression in various diseases (Hsu et al, 2012; Yao et al, 2015; Jung et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…When Nrf2 is up-regulated and translocated into the nucleus from the cytoplasm under stress conditions, the process is also essential for the activation of HO-1 expression (Kang et al, 2015). Growing evidence demonstrated that the Nrf2/HO-1 signaling pathway participated in the process of oxidative stress in several brain dysfunctional diseases (Meng et al, 2016; Bellaver et al, 2017; Zhao et al, 2018). Several antioxidant ingredients indicated that they protected cell damage by up-regulating Nrf2 and HO-1 expression in various diseases (Hsu et al, 2012; Yao et al, 2015; Jung et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results authors assumed that HBOT may diminish the inflammatory response after TBI by inhibiting the activation of inflammasome signaling. Latest results of Meng et al [86] showed that HBOT significantly increased the expression of nuclear factor (erythroid-derived 2)-related factor 2 (Nrf2) and heme oxygenase-1, and inhibited the expression of Toll-like receptor 4 and nuclear factor-kappa B in a rat TBI model [87]. Furthermore, HBOT decreases expression of nNOS, eNOS and iNOS (neuronal, endothelial and inducible nitric oxide synthases) mRNA in the cortex after acute traumatic cerebral injury [92].…”
Section: Hbot Prevents Spreading Of the Neuroinflammation In The Injured Tissuementioning
confidence: 99%
“…Data of many studies has been shown that HBO suppress various mediators of inflammation [54,67,86,87] indicating that the decreased brain edema, blood-brain barrier leakage, cell…”
Section: Hbot Prevents Spreading Of the Neuroinflammation In The Injured Tissuementioning
confidence: 99%
“… 102 HBOT increased expression of the heme oxygenase, nuclear factor erythroid 2-related factor 2 (Nrf2), and quinine oxidoreductase 1 in the brain tissue around the lesion and also improved neurological function after TBI. 103 A study revealed that HBO reduces IL-1β and IL-18 and suppresses protein expression of inflammasome components, along with high-mobility group box 1 reduction after TBI in the brain and serum. 104 In regard to repetitive mild TBI, it was found that HBOT significantly decreased the magnetic resonance imaging-identified abnormalities and tissue histopathology.…”
Section: N V Ivo S Tudiesmentioning
confidence: 99%